Intrapulmonary bronchogenic cyst: Single case report - How, Soon Hin; Tee, Hoi-Poh; Muhammad, Amran; Abdul Rani, Mohammed Fauzi (University Malaya, 2008)
Intrapulmonary bronchogenic cyst is a rare congenital lesion originating from abnormal budding of the embryonic foregut. It is less common than mediastinal bronchogenic cyst. We describe a case of intrapulmonary bronchogenic cyst and discuss the treatment of this condition.